Influence of feeding practices on Childhood illness - Lokesh, Nagendra; Kulkarni, Praveen; Basheer, Sayana; Rajaram, Pragadesh; Anbu, Vanmathi; Kumar Doddaiah, Sunil (Indian Journal of Community Health, 2024)
Background: The phase between a child's birth and the age of two years is crucial for ensuring the child’s growth and development through optimal feeding habits. Breastfeeding is considered one of the most effective methods for ensuring the health and survival of children. Aim & Objective: This study aims to access the influence of feeding practices on childhood illness. Methodology: A cross-sectional study was done among 280 mothers having children less than 2 years of age attending primary health centres adopted by the Department of Community Medicine JSS medical college, Mysuru. Data regarding feeding practices and childhood illnesses were collected using a pre-tested questionnaire prepared based in Infant and Young Child Feeding guidelines by interviewing the mothers. Result: Among the study population, 75.4% of children in urban and 75.7% of children in rural suffered from childhood illness. It was observed that childhood illness was more common among children with poor feeding practices (75.7% in rural and 93.5% in urban) and the association was found to be statistically significant. Conclusion: The study sheds light on the importance of appropriate feeding practices, which have a higher influence on a child's health.